Design, synthesis, molecular docking, and molecular dynamic studies of novel quinazoline derivatives as phosphodiesterase 7 inhibitors - El-Malah, Afaf A.; Gineinah, Magdy M.; Khayat, Maan T.; Aljahdali, Anfal S.; Safar, Marwa M.; Almazmumi, Hadeel A.; Khinkar, Roaa M. (Frontiers in Pharmacology, 2024)
Phosphodiesterase 7 (PDE7) is a high-affinity cyclic AMP (cAMP)-specific PDE that is expressed in immune and proinflammatory cells. In this work, we explore the possibility that selective small molecule inhibitors of this enzyme family could provide a novel approach to alleviate the inflammation that is associated with many inflammatory diseases. A series of novel substituted 4hydrazinoquinazoline derivatives and fused triazoloquinazolines were designed, synthesized, and evaluated in vitro for their PDE7A inhibition activities, in comparison with Theophylline, a nonselective PDE inhibitor, and BRL50481, a selective PDE7A inhibitor. This series of novel quinazoline derivatives were synthesized via multi-step reactions. The reaction sequence began with selective monohydrazinolysis of compounds 2a,b to give 3a,b. Schiff bases 4a-h were synthesized by the reaction of the quinazolylhydrazines 3a,b with various substituted aromatic aldehydes. The reaction of 4a-h with bromine in acetic acid, in turn, gave fused triazoloquinazolines 5a-h. These compounds were characterized by satisfied spectrum analyses mainly including 1 HNMR, 13 CNMR, and MS together with elemental analyses. The results of in vitro PDE7A inhibition activity clearly indicated that compounds 4b, 4g, 5c, and 5f exhibited good potency. Molecular docking and molecular dynamic simulation studies further supported our findings and provided the basis of interaction in terms of conventional hydrogen bonds and π-π stacking patterns. The present results lay the groundwork for developing lead compounds with improved phosphodiesterase 7 inhibitory activities.